Integration of Intangible Cultural Heritage Elements into Furniture Design Based on Symbolic Semantics and AHP: A Case Study of Qianci - Jiahang Chen; Huimei Xia; Shun Yu (BioResources)
This study explored methods for integrating intangible cultural heritage (ICH) elements into modern furniture design, using Qianci as an example. Through symbolic semantics analysis, the cultural external layers of form, color, craftsmanship, and composition and the cultural internal layers of symbolic meaning, ideology, religious beliefs, and moral ethics of Qianci symbols were interpreted, extracting core design elements suitable for modern furniture design. Based on the Analytic Hierarchy Process (AHP), a hierarchical model was established to integrate intangible cultural heritage symbols with furniture design, quantitatively analyzing the importance of key elements in the design process. The results indicate that cultural symbolism, form design, cultural element integration, decorative patterns, cultural heritage value, and environmental friendliness are key indicators in furniture design. Accordingly, two thematic furniture design proposals were developed and evaluated, confirming the innovative potential and application value of Qianci symbols in modern furniture design. This study provides new perspectives and practical examples for the revitalization of intangible cultural heritage elements and the diversification of furniture design.